Pengaruh Strategi Pemasaran Dan Kualitas Produk Terhadap Pengembangan Usaha Seblak - Mia Maulida; Sisca Septiani (Transformasi: Journal of Economics and Business Management, 2023)
This study aims to analyze the influence of marketing strategy and product quality on the development of the Seblak Teh Hanan business in Parakanlima Village, Jatiluhur District, Purwakarta City. The source of data in this study was obtained from questionnaires (primary) which were distributed to respondents. The population of this research is the consumers of Seblak Teh Hanan . The research sample amounted to 99 people. The research analysis method used is validity test, reliability test, normality test, multiple linear regression, f test and t test and coefficient of determination. The research findings show that the marketing strategy and product quality simultaneously affect business development with the results of the Fcount test of 145.528 and a significance value of <0.05. Based on multiple linear regression analysis, the coefficient of determination is 75.2%. The t-test value of the marketing strategy variable is 3.372 and the t-test value of the product quality variable is 8.102, both variables have a significance of <0.05 so it can be concluded that partially the two independent variables affect the dependent variable.